Expectations and Stability in the Kaleckian Growth Model - Lima, Gilberto Tadeu; Setterfield, Mark (Brazilian Keynesian Review, 2016)
A central element in the canonical Kaleckian growth model is the demand-led output-adjustment stability condition known as the Keynesian stability condition. This condition requires that, all else constant, saving be less responsive to changes in capital capacity utilization than investment. This paper further explores the plausibility of the Keynesian stability condition by enriching the Kaleckian growth model with a more fully developed Keynesian theory of expectations formation. As a result, the responsiveness of investment to changes in capacity utilization is reduced, and through mechanisms that have clear and plausible behavioural underpinnings. It therefore becomes more likely (in principle) that the Keynesian stability condition will hold in practice. The paper also explores the consequences of such re-specification of investment behaviour for certain comparative static results associated with the canonical Kaleckian growth model.